Familial Mediterranean fever with colonic lesions: A case report - Hiroyuki Ariga; Reiko Kunisaki; Takeshi Ojima; Satoshi Suzuki; Kenta Okada; Junya Kashimura (DEN Open)
Abstract A 26‐year‐old man with a history of ulcerative colitis treatment presented to our clinic with abdominal pain and fever. He had a history of bloody stools and abdominal pain at 19 years of age. A thorough examination by a medical practitioner, including lower gastrointestinal endoscopy, resulted in the diagnosis of ulcerative colitis. After induction of remission with prednisolone (PSL), the patient was treated with 5‐aminosalicylate. One year ago in September, his symptoms flared up again, and he was administered 30 mg/day of PSL until November of the same year. However, he was transferred to another hospital and referred to his previous doctor. During the follow‐up in December of the same year, flare‐ups of abdominal pain and diarrhea were reported. Upon review of the patient's medical history, familial Mediterranean fever was suspected because the patient had periodic fevers ≥38°C and symptoms that persisted even after oral steroid administration and were sometimes accompanied by joint pain. However, he was transferred again, and PSL was administered once more. The patient was referred to our hospital for further treatment. At the time of arrival, his symptoms did not improve with 40 mg/day of PSL, and endoscopy and computed tomography revealed thickening of the colon, with no abnormality in the small intestine. Suspecting familial Mediterranean fever‐associated enteritis, the patient was administered colchicine, resulting in an improvement in symptoms. Furthermore, an examination of the MEFV gene showed a mutation in Exon5 (S503C), and atypical familial Mediterranean fever was diagnosed. Endoscopy after colchicine treatment revealed that the ulcers improved remarkably.